2019
DOI: 10.3390/ani9121050
|View full text |Cite
|
Sign up to set email alerts
|

Using Genetics to Evaluate the Success of a Feral Cat (Felis catus) Control Program in North-Western Australia

Abstract: Simple Summary: The management of invasive species is a major challenge for the conservation of biodiversity globally. One technique that has been widely used to control feral cats (Felis catus) and red foxes (Vulpes vulpes) in Western Australia is the aerial broadcast of toxic baits, but assessing its efficacy can be difficult. Here, we report on a method of evaluating the effectiveness of this method for the abatement of feral cats using genetic analysis techniques. However, our results were unable to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Differences in the mean PCV values were statistically significant (Student's t-test, P = 0.037), such that the mean PCV was 28.2% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] for positive cats and 34.6% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] for negative cats (Table 1). Although hemoplasmas have been shown to be opportunistic pathogens associated with arthropod-borne diseases, 37 previous studies on the same cat population found anti-T gondii (Fisher's exact test, P = 0.06), anti-Rickettsia rickettsii (Fisher's exact test, P = 0.07) and anti-R parkeri (P = 0.38) antibodies that did not present any associated risk factor for coinfection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the mean PCV values were statistically significant (Student's t-test, P = 0.037), such that the mean PCV was 28.2% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] for positive cats and 34.6% (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] for negative cats (Table 1). Although hemoplasmas have been shown to be opportunistic pathogens associated with arthropod-borne diseases, 37 previous studies on the same cat population found anti-T gondii (Fisher's exact test, P = 0.06), anti-Rickettsia rickettsii (Fisher's exact test, P = 0.07) and anti-R parkeri (P = 0.38) antibodies that did not present any associated risk factor for coinfection.…”
Section: Resultsmentioning
confidence: 99%
“…This may impair extrapolation of the findings to the whole population, particularly with regard to free-roaming cats. 30 This small, free-roaming cat sample was a result of difficulties in catching the cats, 32 together with the potential *Indirect immunofluorescence assay was used to determine serological status 30,31 OR = odds ratio; CI = confidence interval; FIV = feline immunodeficiency virus; FeLV = feline leukemia virus risk to life posed by trapping, the temporary duration of permission for sampling from the campus and an excess of cat food offered by visitors to the campus at several (more than 40) campus locations, which strongly competed with cat bait traps. A more representative free-roaming cat sample is needed in future studies, and this should extend to other university campuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different classes of molecular markers have been employed in invasive species research, historically including protein-based allozymes, polymorphic nuclear and organellar DNA fragments [e.g., restriction/amplified fragment length polymorphisms (RFLPs/AFLPs), mitochondrial/chloroplast DNA (mtDNA/cpDNA), respectively], and hypervariable tandemly repeated DNA sequences (e.g., microsatellites and minisatellites; Le Roux and Wieczorek, 2009). Microsatellites and mtDNA, in particular, have seen frequent application in IMS research (Browett et al, 2020), although they may not be sensitive enough to reconstruct invasion histories and delineate eradication units in recently diverged populations or those exhibiting contemporary gene flow (Cowen et al, 2019;Yoshida et al, 2020).…”
Section: Genetic and Genomic Tools For Informing The Study And Management Of Invasive Speciesmentioning
confidence: 99%
“…From an economic perspective, it is essential that we measure the outcomes of the pre- and post-management abundance of cats. Cats can breed rapidly, potentially doubling in abundance each year [ 25 ], and disperse over long distances [ 26 , 27 ]. This allows populations of feral cats to potentially recover quickly post-management.…”
Section: Introductionmentioning
confidence: 99%